ANALISIS STRUKTUR ORGANISASI TERHAADAP KOORDINASO KERJA PADA KANTOR CAMAT SIANTAR MARTOBA PEMATANGSIANTAR - RISMA NURHAINI MUNTE (LP2MTBM MAKARIOZ, 2019)
This study aims to determine the analysis of the organizational structure of the coordination of work at the Office of the Subdistrict of Siantar Martoba Pematangsiantar. This research was conducted at the Office of the Subdistrict of Siantar Martoba Pematangsiantar located in the area of Rev. J.Wismar Saragih Pematangsiantar. Based on the observations of the researcher, the method used is the Eksplanotory Survey research method, namely that the research explaining the contents highlights the relationship between the research variables and examines the hypotheses that have been prepared previously. Data collection techniques used for this study are literature studies, namely collection techniques that are carried out by studying and reviewing problems through books, documents or other written material that has to do with what is being studied, namely the following techniques: observation, interviews and questionnaires or questionnaire distributed to respondents with sklala likert. The organizational structure used by the Siantar Martoba Pematangsiantar Sub-District Office clarifies the coordination relationship between each part of the agency so that each person knows the part that interacts in the overall operational process. Coordination is carried out throughout all levels according to their respective sections, starting with the sub-district level, secretary of the sub-district head, head of sections and sub-sections. Horizontal coordination in the office of the Siantar Martoba Sub-district Head Office of Pematangsiantar has been going well, where the leadership doubts the subordinates' ability to delegate authority (eg from the copat, sub-district secretary, head of section and sub-section to field staff).